The Crafty Chica creates! : Latinx-inspired DIY projects with spirit and sparkle - Cano-Murillo, Kathy (Quarry Books, an imprint of The Quarto Group, 2021)
"The Queen of Latina Style, Kathy Cano Murillo, is back with fantastic art and craft projects--including brand-new ideas and previous favorites--in The New Crafty Chica Collection"--